Social descent with territory loss causes rapid behavioral, endocrine and transcriptional changes in the brain - Maruska, Karen P. (Company of Biologists, 2013)
In social species that form hierarchies where only dominant males reproduce, lower-ranking individuals may challenge higher-ranking ones, often resulting in changes in relative social status. How does a losing animal respond to loss of status? Here, using the African cichlid fish Astatotilapia burtoni, we manipulated the social environment, causing males to descend in rank, and then examined changes in behavior, circulating steroids and immediate early gene (IEG) expression (cfos, egr-1) in micro-dissected brain regions as a proxy for neuronal activation. In particular, we examined changes in the conserved ‘social behavior network’ (SBN), a collection of brain nuclei known to regulate social behaviors across vertebrates. Astatotilapia burtoni has rapidly reversible dominant–subordinate male phenotypes, so that within minutes, descending males lost their bright body coloration, switched to submissive behaviors and expressed higher plasma cortisol levels compared with non-descending and control males. Descending males had higher IEG expression throughout the SBN, but each brain region showed a distinct IEG-specific response in either cfos or egr-1 levels, but not both. Overall, SBN IEG patterns in descending males were distinctly different from the pattern observed in males ascending (subordinate to dominant) in social status. These results reveal that the SBN rapidly coordinates the perception of social cues about status that are of opposite valence, and translates them into appropriate phenotypic changes. This shows for the first time in a non-mammalian vertebrate that dropping in social rank rapidly activates specific socially relevant brain nuclei in a pattern that differs from when males rise to a higher status position.